1994
DOI: 10.1038/eye.1994.91
|View full text |Cite
|
Sign up to set email alerts
|

Oral tetracycline in the treatment of recurrent corneal erosions

Abstract: We report the results of a prospective, randomised controlled, 24 week trial to assess the efficacy of oral tetracycline and oral tetracycline with topical prednisolone in the treatment of recalcitrant recurrent corneal erosions, i.e. those which fail to respond to standard therapy. A total of 30 patients were randomly allocated to either standard treatment (group A), standard treatment and oral tetracycline (group B) or standard treatment, oral tetracycline and topical prednisolone (group C). Treatment groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Previous studies have shown that RCE are associated with chronic blepharitis and acne rosacea. 6,42 Appropriate therapeutic measures such as lid hygiene and oral tetracyclines are useful in reducing episodes of RCE. 6,42 Tetracylines not only reduce the free fatty acids in the tear pool of patients with meibomian gland dysfunction, but also reduce the number of colony forming units cultured from the eyelids.…”
Section: Management Of Rcementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that RCE are associated with chronic blepharitis and acne rosacea. 6,42 Appropriate therapeutic measures such as lid hygiene and oral tetracyclines are useful in reducing episodes of RCE. 6,42 Tetracylines not only reduce the free fatty acids in the tear pool of patients with meibomian gland dysfunction, but also reduce the number of colony forming units cultured from the eyelids.…”
Section: Management Of Rcementioning
confidence: 99%
“…45 Both topical steroids and oral doxycycline were reported to decrease the frequency of RCE in one randomised controlled clinical trial. 42 The corneal epithelium produces gelatinase B (metalloproteinase À9) an enzyme that plays a role in the wound healing process. 44,46 Gelatinase B has been detected in the corneal basal epithelial cells at the edges of non-healing corneal ulcers in humans.…”
Section: Inhibitors Of Mmpmentioning
confidence: 99%
“…Several alternative techniques, in addition to conservative measures, have been developed for the treatment of patients who have recurrences; these include mechanical debridement, ASP using a needle, Nd-YAG laser or diamond burr, superficial keratectomy or PTK [9][10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatment in cases of post-LASIK recurrent epithelial defects and epithelial loosening includes lubrication, application of topical hypertonic agents, use of topical corticosteroids to reduce the risk of deep lamellar keratitis (DLK), autologous serum, administration of oral tetracyclines, and patching or application of therapeutic contact lenses. Invasive measures in the management of recalcitrant corneal erosions include needle or Nd:YAG laser-induced anterior stromal micropuncture (ASP), phototherapeutic keratectomy (PTK) and superficial keratectomy [9][10][11][12][13][14][15][16][17]. ASP may be helpful for preventing future recurrent epithelial defects and possibly DLK [18].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding medical therapy, given the inhibitory activity of the extracellular matrix degradation by metalloproteinases, oral tetracyclines and topical corticosteroids, alone or in a combination regimen, have been proposed and found effective in reducing symptoms and recurrences compared with standard therapy 13 14. Autologous serum therapy, providing fibronectin, is thought to promote epithelial migration and anchorage and was also used in patients with refractory RCES 15…”
mentioning
confidence: 99%